2017
DOI: 10.1007/s11060-017-2407-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving the utility of 1H-MRS for the differentiation of glioma recurrence from radiation necrosis

Abstract: Proton magnetic resonance spectroscopy (H-MRS) has shown promise in distinguishing recurrent high-grade glioma from posttreatment radiation effect (PTRE). The purpose of this study was to establish objective H-MRS criteria based on metabolite peak height ratios to distinguish recurrent tumor (RT) from PTRE. A retrospective analysis of magnetic resonance imaging andH-MRS data was performed. Spectral metabolites analyzed included N-acetylaspartate, choline (Cho), creatine (Cr), lactate (Lac), and lipids (Lip). Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…MRS is a noninvasive MR-based imaging technique that provides data on cellular metabolism. Plenty of published studies have confirmed that MRS can not only improve the diagnostic accuracy of glioma, grade the tumor, but also identify the radioactive necrosis and recurrence and predict survival rate [34]. There was a strong connection between the Cho/Cr and Lac and TERTm in our study.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…MRS is a noninvasive MR-based imaging technique that provides data on cellular metabolism. Plenty of published studies have confirmed that MRS can not only improve the diagnostic accuracy of glioma, grade the tumor, but also identify the radioactive necrosis and recurrence and predict survival rate [34]. There was a strong connection between the Cho/Cr and Lac and TERTm in our study.…”
supporting
confidence: 72%
“…Though Lip peak was verified to be associated with the activity of tumor necrosis [38], there was no predictive value demonstrated in our research, which may be due to the Lip peak Applying radiomics nomogram for prediction, the probability of TERT promoter mutation was close to 0.9. BioMed Research International being more sensitive to the placement of voxels, thus affecting the definitive results [34]. Therefore, it is necessary to conduct a further study on the Lip feature for predicting TERT promoter mutations.…”
mentioning
confidence: 99%
“…The problem of imbalanced classes has also been tackled with the use of AdaBoost . Supervised pattern recognition techniques such as support vector machines, linear discriminant analysis or several different algorithms, and classifier fusion, are also used in the latest literature, mainly for diagnostic questions. These methodologies are, generally too sophisticated to be put in practice by purely clinical groups, and when methodologies are tested the norm is availability of very small datasets, although there are exceptions such as Reference 113 or 109.…”
Section: Mrs Cancer Patternmentioning
confidence: 99%
“…On the other hand, groups from clinical centres tend to use simpler approaches on larger series of patients from one clinical setting. In Reference , Crain et al measured five peak heights with ImageJ directly over the image provided by the scanner software, to apply a linear discriminant classifier on SPSS, testing different ratio combinations, to differentiate between post‐radiation effects and recurrence in gliomas, however with low success. In Reference , principal component analysis, a feature extraction method, is used to successfully visually distinguish one genetically different type of medulloblastoma of the four already accepted existing subtypes .…”
Section: Mrs Cancer Patternmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy ( 1 H MRS) allows noninvasive assessment of metabolic alterations within a tissue of interest. 1,2 A number of studies [3][4][5][6][7][8][9] have reported the utility of 1 H MRS for studying brain tumor metabolism. These studies have reported promising results in evaluation of glioma grade, identification of glioma genotypes, differentiation of neoplasm types, differentiation of recurrent tumors from radiation injury, and assessment of the effect of whole brain radiation therapy on normal brain parenchyma in patients with metastases.…”
Section: Introductionmentioning
confidence: 99%